A new method for the preparation of 1,3-dilithiopropyne: an efficient synthesis of homopropargyl alcohols - Cabezas Pizarro, Jorge A. (2001)
Controlled dilithiation of propargyl bromide with two equivalents of n-butyllithium, in the presence of TMEDA, produces the operational equivalent of the dianion 1,3-dilithiopropyne. The latter reacts efficiently with aldehydes and ketones to produce homopropargyl alcohols in a single step route and in high yields. Controlled dilithiation of propargyl bromide with n-BuLi, in the presence of TMEDA, produces the operational equivalent of the dianion 1,3-dilithiopropyne. The latter reacts efficiently with aldehydes and ketones to produce homopropargyl alcohols in a single step route in high yields.